2019 4th International Conference on Computer Science and Engineering (UBMK) 2019
DOI: 10.1109/ubmk.2019.8907102
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain-Based Electronic Voting System for Elections in Turkey

Abstract: Traditional elections satisfy neither citizens nor political authorities in recent years. They are not fully secure since it is easy to attack votes. It threatens also privacy and transparency of voters. Additionally, it takes too much time to count the votes. This paper proposes a solution using Blockchain to eliminate all disadvantages of conventional elections. Security and data integrity of votes is absolutely provided theoretically. Voter privacy is another requirement that is ensured in the system. Lastl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 9 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…Regarding to a previous study called Blockchain-Based Electronic Voting System for Elections in Turkey [36], it has been observed that in its system all the voting information is kept in the highest level blocking chain, so that the voting information of the whole country can be instantly accessible at any time after it is synchronized. Thus, it will not be a problem to explain the election results, and it will save a lot of time that is being spent to count the votes.…”
Section: About the Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding to a previous study called Blockchain-Based Electronic Voting System for Elections in Turkey [36], it has been observed that in its system all the voting information is kept in the highest level blocking chain, so that the voting information of the whole country can be instantly accessible at any time after it is synchronized. Thus, it will not be a problem to explain the election results, and it will save a lot of time that is being spent to count the votes.…”
Section: About the Case Studymentioning
confidence: 99%
“…Thus, it will not be a problem to explain the election results, and it will save a lot of time that is being spent to count the votes. This was used to change the old inefficient system and will bring a modern and efficient system to Turkey, and will also lead to saving a lot of energy and money across the nation [36]. Although the work done in the mentioned study had a positive result, the present one is considered more accurate in comparison since relevant data have been taken into consideration such as the viability of the project in urbanized areas, making it more realistic since it must be taken into account that not all the population can access the Internet, and therefore the proposed tool.…”
Section: About the Case Studymentioning
confidence: 99%
“…In another study focusing on the Middle East, Ozturan, Atasu, and Soydan (2019) [19] highlighted that Turkish banks' readiness to adopt the blockchain technology was at a mean of 3.30. In a similar perspective, Bulut, Kantarcı, Keskin, and Bahtiyar (2019) [10] examined the efficiency of blockchain technology by testing the time it takes to conduct an election. The results revealed that the technology significantly minimized waiting time for results.…”
Section: Blockchain Technology In the Middle Eastmentioning
confidence: 99%
“…The democratic frameworks have created over the long haul, as has the security weakness. Vote fixing, EVM (Electronic Voting Machine) hacking, surveying stall catch, and political decision control are the main points of contention that should be addressed in the current democratic framework [1,10]. The idea of I-voting (internet voting), which allows for a secure balloting process, is being promoted by the revolution in voting systems in several countries.…”
Section: Introductionmentioning
confidence: 99%